Heparan sulfate proteoglycans remodel SARS-CoV-2 spike conformation to allow integrin interaction and infection of endothelial cells - Bugatti, Antonella; Zani, Alberto; Bardelli, Marta; Giovanetti, Marta; Ravelli, Cosetta; Ciccozzi, Massimo; Caruso, Arnaldo; Caccuri, Francesca (Frontiers in Cellular and Infection Microbiology, 2025)
SARS-CoV-2 infects ACE2-negative primary HL-mECs through the interaction of an RGD motif, included in all spike proteins, up to the Omicron BA.1 subvariant, with αvβ3 integrin. Following its entry, SARS-CoV-2 remodels ECs phenotype and promotes angiogenesis in the absence of productive viral replication. Moreover, lack of spike/αvβ3 interaction, occurring in Omicron BA.5 which contains the D405N mutation in the RGD motif, inhibits HL-mECs infection and dysfunction. It is worth noting that anti-spike antibodies do not impact SARS-CoV-2 entry into HL-mECs. This data highlights the fact that i) the RGD motif is not exposed in the entire spike protein and ii) the need of a cofactor favoring spike/αvβ3 interaction. HSPGs are used by different viruses as receptors and coreceptors for their entry into host cells. Here, we use different approaches to scrutinize the role exerted by HSPGs in favoring SARS-CoV-2 infection of ECs. We highlight HSPGs as key molecules responsible for RGD exposure allowing its binding to the αvβ3 integrin as the first step toward viral entry by endocytosis. Indeed, SPR analysis showed lack of spike/αvβ3 interaction in the absence of heparin. This data was further corroborated by immunofluorescence and infectivity assays. Interestingly, the use of Heparinase III or sodium chlorate counteracts the release of proangiogenic molecules and inhibits signaling pathways induced by SARS-CoV-2 infection. Thus, HSPGs may represent a target for preventing SARS-CoV-2 infection of ECs and EC dysfunction-related COVID-19 severity.